OʻQUVCHILARDA KREATIV KOMPETENTLIGINI RIVOJLANTIRISH JARAYONI - Odilova Sarvinoz Isoq qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article describes the methodology used in physics lessons to develop students' creative thinking, discusses the importance of a systemically active approach to learning and the development of creative thinking. The article presents creative tasks for students and methods of creating motivation in the educational process. The article includes methodological approaches aimed at increasing the creative abilities of students and their ability to synthesize knowledge.